Profiling Creative Competence, Cultural Literacy, and Career Readiness among Guidance and Counseling Students as a Basis for Developing a Digital-Art and Local-Wisdom Learning Model - Afriyati, Vira; Misbahudin, Arsyadani (KONSELOR, 2025)
This study presents baseline data on the levels of creative competence, cultural literacy, and career readiness among students in the Guidance and Counseling Study Program, informing the design of a learning model that integrates Digital Art and local wisdom. Using a descriptive quantitative design, the study involved 290 students across semesters, genders, and ethnic backgrounds. Data were collected via a validated questionnaire comprising three operationalised competency constructs and analysed using descriptive statistics. Results show that cultural literacy had the highest mean percentage (35.5%), followed by career readiness (33.2%) and creative competence (31.3%), indicating relatively strong cultural understanding. In contrast, creativity and career readiness remain at moderate levels. Descriptive patterns across semesters suggest higher scores in early semesters, with career readiness rising among final-year students. Gender-based differences were minimal, and ethnic-group variations must be interpreted cautiously, given unequal sample sizes. Overall, the findings provide an empirical profile of students’ initial competencies and serve as foundational evidence for developing learning innovations that incorporate digital art and local cultural values.